Effect of Drying on the Textural Attributes of Bell Pepper and Pumpkin - Guiné, Raquel (2012)
The present work evaluates the effect of different drying treatments on the textural attributes of bell peppers (green and red) and of pumpkins (C. maxima and C. moschata), which were dried using different methods: freeze-drying and air drying at different temperatures. From the results obtained it is possible to conclude that with respect to pumpkin, it was not found any dependence between the fiber orientation and the hardness of the fresh vegetable, but a significant dependence was observed on the location of the sample, with those samples situated closer to the skin showing higher values of hardness. As to the bell peppers, the hardness is higher for those measurements made from the external side when compared to those made from the internal side. As to the effect of drying on the texture of the vegetables, it was found that the increase in air drying temperature drastically reduces the hardness of all vegetables and that freeze drying has an intermediate effect between the vegetables dried at 30ºC and 70ºC. Moreover, the springiness tends to be higher in dried bell peppers but no significant effect was observed on this attribute in the case of pumpkins. With respect to cohesiveness, the results are similar to those for springiness, so that it is slightly higher in the dried bell peppers but in the case of pumpkins, no differences were found. Finally, the trends observed for chewiness follow those for hardness in all cases at study.